Factors affecting efficiency of public universities in Nigeria: Evidence from mixed-method approach - Adamu, Mohammad (2020)
Public universities in Nigeria depend heavily on government financing. However, financing continues to be scarcer as the universities continuously receive pressures for enrolment, due to high demand for university education coupled with incessant strike actions from universities’ staff unions. It becomes a concern how these universities utilize their resources. This study assesses the relative efficiency of public universities, and determines the effects of exogenous factors affecting the efficiency of the public universities in Nigeria. The study uses mixed-method of quantitative and qualitative analyses. In the quantitative analysis, Data Envelopment Analysis and Tobit regression are employed. Thematic interviews are conducted in 14 of the 18 universities and with a stakeholder representing the government so as to further answer the objectives of the study. Quantitative results show that only 2 out of the total 18 public universities are found to be fully efficient, positioned at the efficiency frontier line for the five different academic sessions and serve as the benchmark. On average, the relative technical efficiency for all universities over the period is 73.4%. The results also reveal significant difference in efficiency between federal and state universities. State universities are found to be more efficient than federal universities, with an average efficiency of 93.9%. The regression result reveals significant negative effects of funding on efficiency of the public universities. University size is found to be statistically significant and positively related with efficiency, while strike action is found to be negatively affecting the efficiency of public universities. The qualitative findings further reveal that misplacement of priority and inappropriate utilization of fund by the university management, poor quality research by staff, inadequate facilities, frequent disruptions of academic calendars, and poor quality graduates impinge on the efficiency of public universities in Nigeria.